Building a botanical foundation for perennial agriculture: Global inventory of wild, perennial herbaceous Fabaceae species. Issue 4 (5th June 2019) - Ciotir, Claudia; Applequist, Wendy; Crews, Timothy E.; Cristea, Neculai; DeHaan, Lee R.; Frawley, Emma; Herron, Sterling; Magill, Robert; Miller, James; Roskov, Yury; Schlautman, Brandon; Solomon, James; et al.
Societal Impact Statement: Agroecosystems are constantly evolving to meet the needs of a growing population in a sustainable manner. Concerns about ecological impacts of agriculture, including soil loss, have focused attention on crops that provide both agricultural products and ecological services. Perennial, herbaceous crops that live for multiple years and can be harvested mechanically produce large root systems that may reduce soil loss; however, these species are largely absent from agriculture. The diversity of wild, perennial, herbaceous legume species documented by the Perennial Agriculture Project Global Inventory (PAPGI) increases resources available to breeders of perennial, herbaceous legumes, and raises awareness about untapped wild plant diversity in future crop development. Summary: Concerns about soil health and stability are focusing attention on crops that deliver both agricultural products and ecological services. Deep rooted, perennial plants that build soil organic matter, support diverse belowground microbial communities, and produce edible seeds are key components underpinning ecological intensification; however, few perennial, herbaceous crops have been domesticated for food. To facilitate development of edible, perennial, herbaceous crops, including perennial grains, we constructed an online resource of wild, perennial, herbaceous species—the Perennial Agriculture Project Global Inventory (PAPGI;http://www.tropicos.org/Project/PAPGI ). The first component of this project focuses on wild, perennial, herbaceous Fabaceae species. We extracted taxonomic names and descriptors from the International Legume Database and Information Service. Names were added to PAPGI, a special project within the botanical database TROPICOS, where they link to specimen records and ethnobotanical and toxicological data. PAPGI includes 6, 644 perennial, herbaceous Fabaceae species. We built a searchable database, a framework for the ongoing incorporation of more than 60 agriculturally important traits for perennial, herbaceous legumes. Here we highlight food and forage uses for 314 legume species, and toxicological data for 278 species. The novel contribution of PAPGI is its focus on wild, perennial herbaceous species that generally have not entered the domestication process but that hold promise for development as perennial food crops. By extracting botanical information relevant for agriculture we provide a dynamic resource for breeders and plant scientists working to advance ecological intensification of agriculture, and for conservation managers working to preserve wild species of potential agricultural importance. Abstract : Wild, perennial, herbaceous plant species have the capacity to provide both agricultural products and ecological services, such as soil stability and efficient absorption, over multiple years. Although perennial, herbaceous species are common in nature, these species were rarely domesticated. We built a global inventory of wild, perennial, herbaceous species in the legume family (Fabaceae), a resource which includes botanical and agricultural information in an online, accessible, searchable format, in order to facilitate pre‐breeding and domestication of perennial, herbaceous species. This resource will help advance agricultural innovation through the development of novel crops that provide food and ecosystem security.